Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1128/aem.02763-10
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated Regulation of Acetoin Fermentation by Quorum Sensing and pH in Serratia plymuthica RVH1

Abstract: During fermentation of sugars, a number of bacterial species are able to switch from mixed acid production to acetoin and 2,3-butanediol production in order to avoid lethal acidification of their environment, although the regulation of this switch is only poorly understood. In this study, we report the identification of the budAB structural operon, involved in acetoin production in Serratia plymuthica RVH1, and its activation by a LysRtype regulator encoded by budR, immediately upstream of this operon. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 24 publications
(29 reference statements)
2
20
0
Order By: Relevance
“…It is one of thirty basic chemical components that the U.S. Department of Energy has prioritized for development and utilization [3]. [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of thirty basic chemical components that the U.S. Department of Energy has prioritized for development and utilization [3]. [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggested that the QS system likely plays a role in controlling glucose metabolism in V. cholerae. Similarly, the level of acetoin fermentation was also regulated by QS in Serratia plymuthica (19). Detailed signaling cues and molecular determinants leading to the activation of acetoin fermentation, however, are not fully understood.…”
mentioning
confidence: 99%
“…In fact, the latter bacteria follow the mixed-acid fermentation route during the early stages of growth and switch to the 2,3-butanediol route in the late-exponential phase (3,4). This switch is generally viewed as a strategy of these bacteria to prevent excessive medium acidification, and it has been demonstrated that knockout of the 2,3-butanediol pathway indeed results in more-pronounced acidification, early growth arrest, and cell death (5,6).…”
mentioning
confidence: 99%